DEVELOPMENT OF NEW GROUNDWATER SOURCES FOR DRINKING WATER SUPPLY UNDER CLIMATE CHANGE CONDITIONS: (on the example of groundwaters in the upper reaches of the Aghstev River) (Proceedings of the YSU C: Geological and Geographical Sciences, 2025)
Тhe natural flow of water resources is decreasing annually due to global warming. Under the current conditions, the development of new groundwater sources for the settlements of Armenia is becoming an important task. The article reviews methods for assessing natural and operational groundwater resources based on hydrogeological studies conducted in the basin of the upper reaches of the Aghstev River, in the middle of the settlements Margahovit and Fioletovo of the Lori Region of the Republic of Armenia. Groundwaters of the artesian basin can be operated by gravity for drinking water supply of Dilijan and other settlements located downstream of the Aghstev River. In the settlements of the northern and southern regions of the Republic of Armenia, located outside the Central Volcanic Highlands, groundwater reserves are insufficient to ensure drinking water supply. Therefore, river water intakes are used here. However, river waters are subject to anthropogenic impact and pollution during seasonal floods. The Margahovit groundwater basin is composed of Quaternary lake-river sediments, represented by alternating layers of loose-fragmental and clayey rocks with an average thickness of 165 m. In the basin, a groundwater aquifer and two confined aquifers have been identified. The confined aquifers, which are hydraulically interconnected and have the same qualitative characteristics, are of practical importance for drinking water supply. This work presents the geological and hydrogeological conditions of the upper reaches of the Aghstev River. The groundwater operational reserves for drinking water supply to the settlements are calculated and substantiated. Methods for treating water with high levels of iron, manganese, and fluoride are presented.
Keywords: groundwater run-off; groundwater natural resources; flow filtration